Reinterpretation of Prophetic Stories in Shaping Modern Business Ethics in the Islamic World - Saona, Saona (Islamic Civilization and History, 2024)
The ethical landscape of modern business practices is increasingly influenced by historical narratives, particularly those derived from religious texts. This study examines the reinterpretation of prophetic stories in shaping contemporary business ethics within the Islamic world. The primary aim is to explore how these narratives can inspire ethical decision-making among Muslim entrepreneurs in the 21st century. A qualitative research approach was employed, utilizing semi-structured interviews with Islamic scholars and business leaders and document analysis of prophetic teachings and relevant literature. The findings reveal that key ethical principles such as honesty, justice, and accountability, exemplified in prophetic stories, are highly applicable in today’s business environment. Participants emphasized the importance of these values in navigating modern ethical dilemmas and fostering a culture of integrity within their organizations. This research highlights the potential of prophetic teachings to guide ethical business practices and instill a sense of responsibility among the youth. By integrating these historical narratives into contemporary education and training, this study aims to contribute to the development of a framework for ethical business conduct rooted in Islamic values.